The Effect of Quality Service and Guest Star on Visitor Satisfaction at The Korean Wave 2022 Event - Ramadhani, Allysa Zahra; Digdowiseiso, Kumba; Husin Demolingo, Ramang (Akademi Komunitas MAPINDO, 2022)
Recently, it is undeniable that tourism is an important sector in Indonesia's economic development. On September 28, 2022, Trans TV again held the Korean Wave 2022 event. This event is a special music event that lasts about three hours as a manifestation of the Korean Wave's application in Indonesia. This music event brought specifically one of the South Korean boy groups as a special performance, namely NCT Dream. The purpose of this study was to determine the influence of guest stars who came and how the role of service quality on the satisfaction of visitors who came to the Korean Wave 2022 event. The type of research used in this study was quantitative research with survey methods. The collection technique in this study was done by distributing questionnaires and analyzing using multiple linear regression analysis. The results of the study found that the Service Quality and Guest Star Partially and Simultaneously influenced Visitor Satisfaction. Keywords: Quality Service, Guest Star, Visitor Satisfaction, and Korean Wave 2022 in Indonesia.